Postradiation Fractures after Combined Modality Treatment in Extremity Soft Tissue Sarcomas. (15th March 2021) - Bartelstein, Meredith K.; Yerramilli, Divya; Christ, Alexander B.; Kenan, Shachar; Ogura, Koichi; Fujiwara, Tomohiro; Fabbri, Nicola; Healey, John H.
Abstract : Soft tissue sarcoma (STS) of the extremities is typically treated with limb-sparing surgery and radiation therapy; with this treatment approach, high local control rates can be achieved. However, postradiation bone fractures, fractures occurring in the prior radiation field with minimal or no trauma, are a serious late complication that occurs in 2–22% of patients who receive surgery and radiation for STS. Multiple risk factors for sustaining a postradiation fracture exist, including high radiation dose, female sex, periosteal stripping, older age, femur location, and chemotherapy administration. The treatment of these pathological fractures can be difficult, with complications including delayed union, nonunion, and infection posing particular challenges. Here, we review the mechanisms, risk factors, and treatment challenges associated with postradiation fractures in STS patients.